Casuística dos exames de diagnóstico por imagem na medicina de animais selvagens - 2009 a 2010 - Bortolini, Z. [UNESP]; Matayoshi, P.m. [UNESP]; Santos, R.v. [UNESP]; Doiche, D.p. [UNESP]; Machado, V.m.v. [UNESP]; Teixeira, C.r. [UNESP]; Vulcano, L.c. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2013)
The aim of this study was to retrospectively evaluate in the casuistry on class and systems frequently diagnosed in wild animals that were sent to the FMVZ-UNESP-Botucatu diagnostic imaging service. The class of birds was the most referred to the centers, followed by the mammals and reptiles. The majority of the requested tests were the radiographs and in a minor scale the tomography and ultrasound. Although the birds were the greatest number of animals sent to the service, mammals were the most radiographed for wound control. The most frequently observed system was the musculoskeletal caused by trauma, especially in birds. The radiograph was the most exam initially indicated, then the animal could be forwarded to other imaging modalities, which in wild animals medicine is still limited to research.
Casuistics of diagnostic imaging in wildlife medicine - from 2009 to 2010
Keywords: ultrassonografia; radiologia; tomografia computadorizada; animais silvestres; diagnóstico por imagem; ultrasonography; radiology; computed tomography; wild animals; diagnostic imaging